p21 promotes error-free replication-coupled DNA double-strand break repair - Mauro, Maurizio (Oxford University Press, 2012)
p21 is a well-established regulator of cell cycle progression. The role of p21 in DNA repair, however, remains poorly characterized. Here, we describe a critical role of p21 in a replication-coupled DNA double-strand break (DSB) repair that is mechanistically distinct from its cell cycle checkpoint function. We demonstrate that p21-deficient cells exhibit elevated chromatid-type aberrations, including gaps and breaks, dicentrics and radial formations, following exposure to several DSB-inducing agents. p21(−/−) cells also exhibit an increased DNA damage-inducible DNA-PK(CS) S2056 phosphorylation, indicative of elevated non-homologous DNA end joining. Concomitantly, p21(−/−) cells are defective in replication-coupled homologous recombination (HR), exhibiting decreased sister chromatid exchanges and HR-dependent repair as determined using a crosslinked GFP reporter assay. Importantly, we establish that the DSB hypersensitivity of p21(−/−) cells is associated with increased cyclin-dependent kinase (CDK)-dependent BRCA2 S3291 phosphorylation and MRE11 nuclear foci formation and can be rescued by inhibition of CDK or MRE11 nuclease activity. Collectively, our results uncover a novel mechanism by which p21 regulates the fidelity of replication-coupled DSB repair and the maintenance of chromosome stability distinct from its role in the G1-S phase checkpoint.